ROLE OF GUILT FORM IN QUALIFICATION OF CRIMINAL OFFENCES CONCEPTUAL AGGREGATION - Persidskis, Ainārs (Administrative and Criminal Justice, 2016)
The topic of the paper is the influence of fault on the qualification of conceptual aggregation of criminal offences. The concept of conceptual aggregation of criminal offences in Criminal Law of Latvia has been more misleading then introduces clarity. The conceptual aggregation of criminal offences is the most difficult type of all multiplicity types of criminal offences. This research paper provides an overview of the influence of fault on the qualification of conceptual aggregation of criminal offences. At the beginning of research paper is given an overview of the concept of fault and an overview of the concept of conceptual aggregation of criminal offenses. After that is given analyses of separate conceptual aggregation qualification cases, assessing the influence of fault on the qualification of conceptual aggregation of criminal offences. At the end of research paper is given conclusions regarding the influence of fault on the qualification of conceptual aggregation of criminal offences.